Psychogenic impact of child labour in Pakistan - Ishaque, Abdul Thawwab; Rizvie, Abdul Raheem; Mohamed Imtiyas, Muhammed Ifham (Journal of the Pakistan Medical Association, 2024)
Madam, Child labour is a pressing global issue, with millions of children affected by its consequences. Currently, millions of children worldwide are trapped in various forms of labour, disrupting their education and robbing them of a proper childhood. Child labour in Pakistan is alarmingly on the rise, with over 3.3 million children trapped in its grasp.1 Approximately 12.5 million children are ensnared in various labour activities, perpetuating a cycle of poverty and denying them their right to education and a proper childhood.2 Shockingly, predictions from the World Economic Forum indicate this number could escalate to 16 million by fiscal year-end.2 A study conducted in three urban squatters of Karachi ., found that behavioural problems afflict 9.8% of working children in Pakistan, with peer and conduct issues being the most prevalent.3 Compounding the concern, Pakistan’s sole National Child Labor Survey in 1996 raises significant doubts about data reliability and comprehensiveness.1 Pakistan’s attempts to combat child labour, including the Convention on the Rights of the Child (CRC) initiated almost three decades ago, have fallen short due to a lack of an established public coordinated child protection case management and referral system, aligned with international standards.4 Legal frameworks and enforcement mechanisms which prohibit child labour such as The Employment of Children Act-1991 exist in Pakistan.5 But they lack the potency needed to effectively curb this pervasive problem due to the persistence of child labour attributed to socioeconomic factors, restricted educational access, and insufficient social support systems. To effectively address this crisis on a long-term basis, a multi-pronged strategy is essential. Strengthening and rigorously enforcing child labour laws is paramount to shielding children from violence and exploitation. A comprehensive legislation incorporating a child protection case management system and referral mechanism is imperative, ensuring children’s rights, quality education, and safeguarding against exploitation. Focused interventions must enhance education access in underserved communities, providing viable alternatives to child labour. Raising awareness among parents, communities, and employers about the enduring harm of child labour is vital. Collaborative endeavours involving governmental bodies, NGOs, and international partners are pivotal for successful implementation and sustainability. An urgent need exists for an updated national child labour survey, reflecting the current socio-economic context to inform future decisions. In summary, urgent action is needed to address Pakistan's child labour's psychological toll. A multifaceted strategical approach can pave the way for a brighter future for every child.